Training or Improvisation?: Citizen journalists and their educational backgrounds—a comparative view. (16th March 2017) - Kus, Michal; Eberwein, Tobias; Porlezza, Colin; Splendore, Sergio
Abstract : While citizen journalists hope to bring new impulses to mass media performance, it is often asked whether they are adequately trained for the production of "newsworthy" stories. This paper focuses on educational aspects of citizen journalism, which, to date, have largely been disregarded by empirical research. A comparative analytical design illustrates the different ways in which citizen journalists acquire and develop the skills that are necessary to undertake journalistic activities in the different journalism cultures throughout Europe. The authors carried out a multi-national analysis in six European countries (United Kingdom, Germany, Austria, Switzerland, Italy, and Poland). In each country, an extensive desk study helped to map the field of citizen journalism and highlight the most relevant examples. Semi-structured interviews with 54 practitioners in the field (representing different types of citizen journalism) made it possible to identify the alternative strategies that citizen journalists employ to prepare themselves for news production initiatives. The research demonstrates that the educational backgrounds of citizen journalists display differences as well as similarities—both within and across journalism cultures. While some of the actors in the field have a clear idea of what constitutes good journalism (and sometimes even aspire to work in a mainstream media organization), others seem to care little about journalistic standards and have only a vague idea about the identity of the profession. On the basis of these insights, the paper develops a typology of citizen journalists that takes into account both their education and their journalistic scope.